Inspection of radioactive nuclei of foodstuffs in Saudi Arabia using a NaI(tl) scintillation detector - Entesar H. EL-Araby; Doaa H. Shabaan (Cogent Food & Agriculture)
The foodstuffs contribute to an increase in the internal dose, which causes great danger to the internal organs and public health. The study of the foodstuffs is necessary to make a radioactive basis for foods and to monitor the change of radioactive nuclei within the agricultural soil. The research is concerned with measuring gamma rays and radioactive nuclei within the most consumed foodstuffs in the Jazan region, southwest of the Kingdom of Saudi Arabia. The detector NaI(Tl) was used to measure the activity of radioactive nuclei within food samples. The results showed the presence of radioactivity for Th-232, K-40, and radon daughters within all foodstuffs. The average values of the radioactivity nuclei for Th-232 and K-40 were 17.85 Bq/kg and 5.69 Bq/kg respectively. Every Raeq value fell within the internationally accepted bounds. All Th-232, K-40, and radon daughters’ concentrations were within the UNSCEAR and ICRP-reported acceptable limits. It was found that 36% of the uranium results exceeded the limit allowed under international agreements. The risky parameters Hex, Hin, and Iγ had mean values within the allowed range of less than one. The food’s effective ingestion dosage (EID) was within the suggested range of 1.1 mSv/y. All radiation dose values were within the international exemption limit. The K-40 values in much of the literature were in agreement with the values in this research. Some food samples showed high activity of radioactive nuclei, so it is necessary to conduct periodic studies to follow up on possible changes in radioactivity and to maintain public health.